1995
DOI: 10.1136/jnnp.58.2.232
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chronic limb spasticity with botulinum toxin A.

Abstract: The purpose of this open study was to find out whether botulinum toxin A (BTX-A) relieves the signs and symptoms of chronic limb spasticity. The study comprised 40 patients, aged 12-82 years, with moderate to severe spasticity of the upper (13) or lower limbs (27) refractory to conventional physical and medical treatments. Outcome measures were clinical and blinded videotape assessments of spasticity and motor function. Electromyography guided BTX-A injections were given in one or two sessions at total doses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
54
0
4

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(59 citation statements)
references
References 5 publications
1
54
0
4
Order By: Relevance
“…This may have implications across the large number of centres used in this study. However, previous studies on the use of BoNT-A in post-stroke spasticity have demonstrated an improvement in spasticity [12, 14, 27, 30, 31, 32, 33, 34]. The greater change in spasticity with dysport 1,500 units may be due to the significantly higher baseline scores, which had more scope for change.…”
Section: Discussionmentioning
confidence: 75%
“…This may have implications across the large number of centres used in this study. However, previous studies on the use of BoNT-A in post-stroke spasticity have demonstrated an improvement in spasticity [12, 14, 27, 30, 31, 32, 33, 34]. The greater change in spasticity with dysport 1,500 units may be due to the significantly higher baseline scores, which had more scope for change.…”
Section: Discussionmentioning
confidence: 75%
“…9 Others report a lack of improved function after local 5 or general 6 treatment of lower limb spasticity, whereas others report good results, 32 especially with neurotomy 8,9 or botulinum toxin A. [12][13][14] Hinderer and Gupta 33 emphasized that very few of the functional scales are operational for monitoring changes related to spasticity. Although patients were selected for the studies, the selection criteria were not given.…”
Section: Discussionmentioning
confidence: 99%
“…4 In hemiplegic stroke patients, treating lower limb spasticity has often failed to improve gait significantly. 4 -7 Some good results have been obtained with neurotomy 8 -10 and botulinum toxin A, [11][12][13][14] but only a small percentage of these patients could benefit from such treatments. In these different studies, the authors considered spasticity to produce a disabling posture of the lower limb, impairing gait by stance equinus, or to generate handicap via an unexplained mechanism.…”
mentioning
confidence: 99%
“…Previous open trial studies have reported substantial amelioration in the muscle tone of spastic patients, both in the upper9 11-13 and lower limbs. '0 [13][14][15][16][17][18][19] To confirm the apparent effectiveness of BTX, double blind, placebo controlled studies have been called for, 20 21 and this we set out to do in a population of adult hemiparetic patients with ankle plantar flexor and foot invertor spasticity.…”
mentioning
confidence: 99%